Computational design of a test article to investigate 2-D surface excrescences on a swept laminar-flow wing. (1st January 2014) - Tufts, Matthew W.; Duncan, Glen T.; Crawford, Brian K.; Reed, Helen L.; Saric, William S.
The construction of a spanwise-invariant swept-wing test article designed to facilitate the inclusion of a range of two-dimensional (2-D) step and gap excrescences in flight via an internal articulation mechanism has been completed. Using a finite-element Navier-Stokes solution and a spectrally accurate boundary-layer solver, coupled with stability analyses, the model has been designed to be subcritical to all instabilities except the crossflow instability. The model can be safely flown in a flight experiment, and be mounted in the Klebanoff-Saric Wind Tunnel at Texas A&M University. The model can be tested at multiple angles of attack (pressure gradients), as well as multiple Reynolds numbers, including unit Reynolds numbers typical of transports. Stability behaviour of the test article was designed to be conducive to a thorough examination of the interaction between an inherent crossflow instability and the shear layer created by the step and gap excrescences. The computations and experiments will together provide data and correlations complementing the previous studies of 2-D excrescences on an unswept flat plate and wedges subject to favourable pressure gradients by The Northrop Grumman Corporation. The current paper focuses on the design and stability analyses of the smooth-wing test article, that is, without excrescences present, as a baseline configuration.